A Multidimensional Practice-Based Framework of Interactive Value Formation. (May 2022) - Luyen, Thuy; Shabbir, Haseeb; Dean, Dianne
This study seeks to deconstruct the multidimensionality of the Interactive Value Formation (IVF) process within complex and prolonged Technology-Based Self-Services (TBSSs). Building on practice theory and Service Dominant logic, this framework sheds light on the complexity of practice-based resource integration processes within the IVF process. The findings demonstrate firstly, how IVF can result in both value co-creation and co-destruction and secondly, how these outcomes are influenced by the enactment of practices within the service experience. Finally, this study demonstrates the mediating role of consumer intensity as a function of consumer effort and time during this enactment. The suggested framework emphasizes the role of engagement, as intersecting between resource-based practices and outcomes, and the nested nature of the IVF process. In doing so, the relationship between the multiple outcomes of engagement and variations in loyalty are revealed. The study has implications for service managers responsible for user experience of complex and prolonged TBSSs. Directions for future research can focus on further deconstructing the multi-dimensionality of the IVF process.